Multimodal approach towards understanding the changes in the autonomic nervous system induced by an ultramarathon - Vieluf, S.; Scheer, V.; Hasija, T.; Schreier, P. J.; Reinsberger, C. (Research in Sports Medicine, 2020)
Purpose: Running an ultramarathon can be considered as a multifaceted, intense stressor inducing changes within the autonomic nervous system (ANS). The aim of this study was to examine changes within and across ANS modalities in response to an ultramarathon.